Problems of Compulsory Alienation of Land for State Needs: A Comparative Analysis of the Legislation of Kazakhstan and Western Countries - KALDARBEKULY, Omiruzak; DOSSYMBET, Kaldarbek; YERKINBAYEVA, Lazzat; TAUBAYEV, Baurzhan; TELEUYEV, Galym B.; MUSSANOVA, Nazerke (Journal of Advanced Research in Law and Economics; Vol 10 No 1 (2019): JARLE Volume X Issue 1(39) Spring 2019, 2019)
A number of new economic, political and social conditions, among which are the updated legal framework for ensuring a market economy and establishing private ownership of land, explain the significant changes in the concept and content of land acquisition in Kazakhstan. The public and the private in the property rights are undoubtedly mutually conditioned, these concepts have not only many intersections, but also clashes that reach their climax in the situation of compulsory turning the private property in the public. This article considers the main theoretical aspects of land seizure under the legislation of foreign countries. Determining the general aim of the legislation, the authors made objective scientific conclusions for improving the state-legal regulation of this area.